Effects of Biuret and Lasalocid (Bovatec) Inclusion into a Commercial Mineral Supplement on Growth Performance of Yearling Calves Grazing in the Kansas Flint Hills - M. G. Pflughoeft; Z. M. Duncan; Z. L. DeBord; W. R. Hollenbeck; F. K. Brazle; E. C. Titgemeyer; K. C. Olson; D. A. Blasi (Kansas Agricultural Experiment Station Research Reports, 2023)
Objective:The objective of this experiment was to measure the effects of non-protein nitrogen (NPN; i.e., biuret) or NPN + ruminal modifier (i.e., biuret + lasalocid) inclusion in a commercial mineral mix on growth performance of yearling beef calves grazing in the Kansas Flint Hills. Study Description:Over a two-year period, 742 crossbred steers [initial body weight (BW): 655 ± 52.2 lb] of Texas and Nebraska origin previously backgrounded at the Kansas State Beef Stocker Unit were used in this experiment. The three mineral treatments consisted of a basal supplement (Control), a basal supplement plus biuret (Biuret), and a basal supplement plus biuret and lasalocid (Bovatec; Zoetis, Parsippany, NJ) with a 4 oz/head daily mineral consumption target. Each treatment was randomly assigned to one of 18 pastures with a total of six pastures per treatment. To determine days-to-empty, mineral feeders were checked daily. Mineral feeders were also weighed weekly to determine mineral consumption. At the onset and conclusion of the experiment, pasture weights were taken to determine average initial and average final BW. Results:Total BW gain, average daily gain (ADG), and mineral consumption did not differ (P≤ 0.15). However, final BW did differ between mineral treatments (P≤ 0.03). Likewise, there was an interaction between treatment and week for days-to-empty (P≤ 0.05). The Bottom Line:These data were interpreted to suggest that the addition of biuret or biuret + Bovatec to a commercial mineral supplement may improve the growth performance of yearling beef cattle grazing in the Kansas Flint Hills.
Keywords: stocker; grazing; NPN; non-protein nitrogen